Effect of Osmotic Dehydration on Mechanical and Rheological Properties of Pumpkin Dried with Microwave Method in Reduced Pressure Conditions (Agricultural Engineering, 2016)
The objective of the research was to indicate the impact of sirup type used for osmotic dehydration and the microwaves power for microwave and vacuum drying on the selected mechanical and rheological properties of dried pumpkin. Pumpkin cultivar Rugosa was osmotically dehydrated in three concentrates: apple, aronia and cherry. Initially prepared material was dried with microwave method in the reduced pressure conditions which was within 6-4 kPa at the microwave power which was 240 and 480 W. Dried material was subjected to compression tests and stresses relaxation tests. Compression work values (Pś), cutting work (Pp) and indicators describing material elasticity (a and b) were computed. An initial treatment in the form of osmotic dehydration carried out before microwave drying in the reduced pressure conditions allows obtaining dried pumpkin with a raised resistance to compression and cutting and the decreased elasticity in comparison to dried material obtained from a pumpkin which was not subjected to the initial treatment. Microwaves power influences the values of compression and cutting of dried pumpkin.